ANALISIS PROSES ADMINISTRASI DI DEPARTEMEN MARKETING PADA PT RAGA PERKASA EKAGUNA - Prihandono (JURNAL LENTERA BISNIS, 2024)
This research was conducted to determine the administrative process in the Marketing department at PT Raga Perkasa Ekaguna. The purpose of this research is to determine the obstacles and solutions in solving problems that occur during the administrative process in the Marketing department at PT Raga Perkasa Ekaguna. Data collection techniques through observation and interviews. The observations carried out are collecting observational data about the object that the writer is researching. The author conducted direct interviews with the parties concerned in implementing the administrative process in the Marketing department. There are obstacles that occur in the administrative process in the Marketing department at PT Raga Perkasa Ekaguna, namely the company's lack of experience capability, lack of human resources, inappropriate company software and hardware, lack of company funds, not meeting the required legality, admin and company work experience. client, the company's NPT does not meet the requirements, and the company's CSMS does not meet the minimum CSMS value. The solutions taken to overcome the obstacles that occur are looking for cooperation partners, completing the organizational structure with competent human resources, completing software and hardware, seeking funding from banks and investors, looking for projects that comply with legality, admin, NPT and company work experience, updating CSMS database and complete current evidence from the project.